Developing a professional leadership identity during organisational change in professional youth football - Gibson, L.; Groom, R. (Qualitative Research in Sport, Exercise and Health, 2020)
The purpose of this paper is to investigate the construction of a professional leadership identity of an outsider appointed to implement organisational change within the academy of a professional football club. Data were collected through field notes, informal observations and meetings, formal academy team meetings, in-depth interviews with three co-workers and four semi-structured in-depth participant interviews, which were subjected to an iterative analysis. Findings highlighted how the appraisal of others and their appraisal of the participant were affected by employment vulnerability, and that `identity work` when leading organisational change was intertwined with micro-political literacy and micro-political action. This study furthers understanding of the development of a leadership identity as a fluid and fragmented struggle, by demonstrating that the process of identity construction is emotional work and is entwined in a complex interplay of micro-political literacy and action, and employment vulnerability.